СИСТЕМА КОМПЛЕКСНОЇ ОЦІНКИ І МЕТОД ВИЗНАЧЕННЯ РОБОЧОГО СТАНУ РОЗПОДІЛЬНОЇ МЕРЕЖІ - Su, Shiwei; You, Yiran; Zou, Yu (Інститут електродинаміки НАН України, Київ, 2020)
With the development of intelligent distribution networks and access to distributed energy, the solving the problem of timely and accurate determination of the operating state of the distribution network is an urgent task. Based on an improved analysis of the principle components of the network and statements of a self-organizing neural network, this article proposes the method to evaluate the operating state of medium- and low-voltage distribution networks. At the first step, the system of evaluating indices of the network is formed by advanced component analysis. The evaluation system is grounded on four aspects, including safety, reliability, quality and economy. Next, the self-organizing neural network is used to identify and clean up the data regarding the operating state of the distribution network. At the next step, the indicators are modeled at all levels; the entropy method is applied to calculate the total weight of all indicators. Then the value of each indicator is found and the weak links of the distribution network are determined. At the final stage, the comprehensive assessment of the real operation of the distribution network in Guangxi province is carried out. As shown, the method can effectively reduce the effect of abnormal data and subjectivity factor on the results of evaluating the state of the distribution network. That confirms the feasibility and practicability of the proposed method. References 22, figures 6, tables 6.